(untitled) (SS Multidisciplinary Research Journal, 2024)
This study observes the economic impact of tax revenue and economic growth of Nepal from fiscal year 2012/13 to 2022/23. To get the objectives, relevant time series secondary data were collected from the economic survey, websites of NTC and other sources published by the Ministry of Finance, Inland Revenue Department, Nepal Rastra Bank, World Bank, and previous works done by the scholars. The collected data has been analyzed by using the linear regression model. The result shows that NTC’s total contribution to government funds and tax revenue positively affects GDP. The tax revenue trend has signified the positive trends but is needs to be more adequate to meet the government revenue of Nepal.